A focused review on membrane contactors for the recovery of dissolved methane from anaerobic membrane bioreactor (AnMBR) effluents. (September 2021) - Velasco, Perlie; Jegatheesan, Veeriah; Thangavadivel, Kandasamy; Othman, Maazuza; Zhang, Yang
Abstract: The need for a more sustainable wastewater treatment is more relevant now due to climate change. Production and reuse of methane from anaerobic treatment is one pathway. However, this is defeated by the presence of dissolved methane in the effluent and would be released to the environment, adding to the greenhouse gas emissions. This review paper provided summary and analysis of studies involved in the production of dissolved methane from AnMBR, focusing with actual methane measurement (gas and dissolved) from AnMBR with different types of wastewater. Then more focused discussion and analysis on the use of membrane-based technology or membrane contactors in the recovery of dissolved methane from AnMBR effluent are included, with its development and energy analysis. The dissolved methane removal and recovery rate of membrane contactors can be as high as 96% and 0.05 mol methane/m 2 /h, respectively, with very low additional energy requirement of 0.01 kWh/m 3 for the recovery. Future perspectives presented focus on the long-term evaluation and modelling of membrane contactors and on the membrane modifications to improve the selectivity of membranes to methane and to limit their fouling and wetting, thus making the technology more economical for resource recovery. Graphical abstract: Image 1 Highlights: Additional energy requirement for recovery of dissolved methane is negligible. Long-term operation causes additional resistancesto the membrane contactors. Janus and omniphobic membranes could provide lower wetting and fouling resistances. High net energy and low GHG is achieved if AnMBR is coupled with membrane contactor.